Water and Ionic Balance in Blue Tilapia Oreochromis aureus (Steindacher 1864) - Faris, Rafaa Abdul kareem; Ahmed, Sumaya M. (Iraqi Journal of Aquaculture, 2021)
This study was conducted to study the response of Blue Tilapia Oreochromis aureus to increasing salinity. Abrupt and gradual transfer to higher salinity was done to determine salinity tolerance and survival rates and was found that this fish tolerate the abrupt increasing in salinity between 1.5 – 20 g/l with Lc50 (20.44 g/l). Salinity tolerance increased with gradual increase in salinity as survival rate increased to 90% in salinity 30 g/l. Muscle and gut were used to investigate their role in water and ionic balance and was found that the water content in the muscle decrease with increasing salinity while it increase in the gut. The ionic content (Na+ and K+) increased in both muscle and gut with increasing salinity. This study showed the ability of this fish to change its osmoregulatory ability from hyperosmotic in fresh water to hyposmotic in salt water.